Development and Validation of a Clinical Grading Scale to Assess the Vulvar Region: The Vulvar Architecture Severity Scale. (8th May 2020) - Almadori, Aurora; Zenner, Nicole; Boyle, Deborah; Swale, Victoria; Reid, Wendy; Maclean, Allan; Butler, Peter E M
Abstract: Background: The vulva is composed of aesthetic units that can be affected differently by vulvar conditions. A reliable, comprehensive, and quick-to-use clinical scoring system is required to assess the disease extent in the vulvar area. Objectives: The aim of this study was to develop and validate a grading scale based on the aesthetic unit principle to evaluate the extent of vulvar lichen sclerosus (VLS). Methods: After reviewing photographs of 100 patients affected by VLS, the authors targeted the aesthetic units most frequently affected. The disease signs were recorded and graded in 4 levels of severity (none, mild, moderate, severe) taking into account the vulvar architecture and skin involvement. To validate the scale, 14 observers were asked to apply it to photographs of 25 VLS patients on 2 different occasions. Intra- and inter-observer reliabilities were determined employing Pearson's and intraclass correlation coefficients. Results: A 6-region, 4-point grading system was designed and identified as the Vulvar Architecture Severity Scale (VASS). In all 6 areas, the Pearson's r was greater than 0.9 (mean, 0.994; 95% confidence interval [CI] = 0.992), indicating that the intra-observer reliability of the VASS was consistent over time ( P < 0.001). Intraclass correlation at time 1 was 0.928 (95% CI = 0.910, 0.943) and at time 2 was 0.944 (95% CI = 0.931, 0.996), indicating a high reliability level among different observers. Conclusions: The VASS is a reliable scale to assess the severity of VLS, and it might be considered as an outcome measure in future VLS trials. Level of Evidence: 4: